(untitled) (Medico Legal Update, 2021)
Background and Objectives: Age of injuries have several medicolegal implications including assault, abuse,criminal conjectures etc. Contusions are wounds characterized by effusion of blood into tissue spaces caused by forceful impact of blunt objects. Its colour changes reflect the natural healing process, though these changes donot occur uniformly and depend on the size of contusion, age and physique of the person and also presence or absence of diseases. This study was aimed at estimating the delay in healing of contusions in diabetic, hypertensive and anemic persons by gross examination and objective analyses including examination under Woods lamp, magnification of digital photograph, and histologic changes to validate the age as per available history. Method: This is an autopsy based prospective study over a period of 1 year (Feb 2015-Feb 2016),involving 50 cases of contusions conducted in Department of Forensic Medicine, Govt Medical College Calicut. The data obtained were analysed by SPSS software version 18. Comparison of different components, the level of correlation between various variables and significance of association were determined, and sensitivity and specificity of various method of analyses in determining the age of wounds were established. Conclusion: Grossly,contusions were red < 24 hours old, bluish black on day 2, greenish on day 3 and yellow on day 7 as was seen in magnified digital photograph. There is increasing positive agreement between colour of wound assessed from magnified digital photograph and period of survival from day 1 to day 5-6 and decreases thereafter in normotensives, hypertensives and non diabetic subjects whereas it drops drastically after 7 days in diabetics. The association between colour of contusion under Woods lamp and survival period increased from day 1 to reach maximum on 5-6 days. There is significant positive association between presence of hypertension,as in diabetes, and histological delay in healing of contusions whereas no significant association was found with anemic status.